Identification of collagens types I, III, IV and alpha-SMA and the participation of myofibroblasts in the fibrotic process in equine endometrosis - Costa, L. D. [UNESP]; Dias, M. C. [UNESP]; Alvarenga, M. A. [UNESP]; Sequeira, J. L. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2017)
Endometriosis is a degenerative change of the uterine glands and surrounding stroma, characterized by periglandular arrangement of myofibroblasts and deposition of extracellular matrix (ECM). The aim of this study was to evaluate the expression of collagen type I, III and IV and alpha-smooth muscle actin (alpha-SMA) in equine endometriosis, and investigate the role of myofibroblasts in the progression of these processes. A parallel was made with histochemical techniques of Masson's trichrome, Picrosirius Red under polarized light and Periodic Acid-Schiff (PAS). Twenty four uterine biopsies received by the Veterinary Pathology Service and Animal Reproduction of FMVZ, UNESP, Botucatu, SP, were diagnosed with endometriosis. Histological analysis revealed that the orange dense collagen fibers correspond to type I collagen, being prevalent in inactive and inactive destructive endometriosis. The green loose collagen fibers correspond to type III collagen, and are predominant in active and active destructive endometriosis. In the same processes, a greater amount of periglandular myofibroblasts were observed in comparison to inactive and inactive destructive endometriosis. The presence of these cells in active processes are strongly related to an increased deposition of collagen type III in fibrotic nests. Regarding the basement membrane, the active destructive and active endometriosis shows thickening, apparently not related to an increase in expression of type IV collagen. The active destructive and inactive destructive endometriosis exhibited disruption areas in type IV collagen fibers. Thus, it is noted that the myofibroblasts are related to increased deposition of type III collagen in active fibrotic nests.
Keywords: mare; endometriosis; collagen; myofibroblasts; immunohistochemistry